149k views
0 votes
Which value is equivalent to 7 multiplied by 3 multiplied by 2 whole over 7 multiplied by 5, the whole raised to the power of 2 multiplied by 7 to the power of 0 over 5 to the power of negative 3, whole to the power of 3 multiplied by 5 to the power of negative 9?

User Hoa Le
by
5.9k points

2 Answers

4 votes

Answer:


=1(11)/(25)

Explanation:

To understand this word problem and form an equation, we will go step by step.

A value:
x

is equivalent to 7 multiplied by 3 multiplied by 2:
x = 7*3*5

whole over 7 multiplied by 5:
x=(7*3*2)/(7*5)

the whole raised to the power of 2:
x=((7*3*2)/(7*5))^2

multiplied by 7 to the power of 0:
x=((7*3*2)/(7*5))^2 * 7^0

over 5 to the power of negative 3:
((7*3*2)/(7*5) )^2*(7^0)/(5^(-3))

multiplied by 5 to the power of negative 9:
((7*3*2)/(7*5) )^2*(7^0)/(5^(-3))*5^(-9)

So we have
((7*3*2)/(7*5) )^2*(7^0)/(5^(-3))*5^(-9)


=((3*2)/(5) )^2*((1)/(5^(-3)))^3 *(1)/(5^(9))


=((3*2)/(5) )^2*5^9*(1)/(5^(9))


=((3*2)/(5) )^2


=((6)/(5) )^2


= (36)/(25)


=1(11)/(25)

User Conradkleinespel
by
6.4k points
3 votes

Given problem is 7 multiplied by 3 multiplied by 2 whole over 7 multiplied by 5, the whole raised to the power of 2 multiplied by 7 to the power of 0 over 5 to the power of negative 3, whole to the power of 3 multiplied by 5 to the power of negative 9. which can be written as:


\left((7\cdot3\cdot2)/(7\cdot5)\right)^2\cdot\left((7^0)/(5^(-3))\right)^3\cdot5^(-9)

Now we have to find the equivalent value for that so we will simplify it


\left((7\cdot3\cdot2)/(7\cdot5)\right)^2\cdot\left((7^0)/(5^(-3))\right)^3\cdot5^(-9)



=\left((3\cdot2)/(5)\right)^2\cdot\left((7^0)/(5^(-3))\right)^3\cdot5^(-9)



=\left((3\cdot2)/(5)\right)^2\cdot\left((7^0)/(5^(-3))\right)^3\cdot5^(-9)



=\left((3\cdot2)/(5)\right)^2\cdot\left((1)/(5^(-3))\right)^3\cdot5^(-9)



=\left((3\cdot2)/(5)\right)^2\cdot\left(5^3\right)^3\cdot(1)/(5^9)



=\left((3\cdot2)/(5)\right)^2\cdot5^9\cdot(1)/(5^9)



=\left((3\cdot2)/(5)\right)^2\cdot1



=\left((3\cdot2)/(5)\right)^2



=\left((6)/(5)\right)^2


=(36)/(25)

Hence final answer is
(36)/(25).


User Phil Ryan
by
6.7k points